Axel Hadenius, Roger Henning & Barry Holmström, Tre studier i politiskt beslutsfattande, Stockholm: Almqvist & Wiksell (Acta Universitatis Upsaliensis, vol. 98), 1984, 188 s., 115,00 Skr. - Johansen, Ove (Politica, 1986)
-